Modelling under risk and uncertainty : an introduction to statistical, phenomenological, and computational methods - Rocquigny, Etienne de (Wiley series in probability and statistics, 2012)
"This book aims at giving a new insight on the peculiar mathematical challenges generated by recent industrial safety or environmental control analysis"--Provided by publisher